Journalism and Political Exclusion - DEBRA M. CLARKE (McGill-Queen's University Press, 2014)
After many Western societies began to deregulate their media industries in the 1980s and 1990s, the prominence of public broadcasting organizations was progressively diminished while, at the same time, the fiscal strength of these organizations was â€“ and continues to be â€“ severely undermined. Under neoliberalism, attention was redirected to commercialization and to the appearance of competition, diversity, and plurality, to the extent that it became possible to interpret developments such as the minimally regulated proliferation of radio broadcasting licences and the multiplication of specialty television channels as a new movement in the direction of â€œmedia pluralismâ€ (Cushion 2012b). Together with the accelerated expansion of the internet and its increasing availability through a diverse number of digital platforms (such as laptops, smartphones, and tablets), the resultant media environment of the twenty-first century is readily celebrated by many as â€œa richer and more globally diverse public sphereâ€ (Cushion 2012b: 1; see, for example, McNair 2006). With regard to journalism in particular, Fuller (2010) is led to proclaim a virtual â€œinformation explosionâ€ whereby news is seemingly available from a multitude of richly diverse sources as well as more easily and more speedily obtained at any time of day or night and from any conceivable geographic location.